Nonproteinuric Preeclampsia among Women with Hypertensive Disorders of Pregnancy at a Referral Hospital in Southwestern Uganda - Asiphas Owaraganise; Richard Migisha; Wasswa G. M. Ssalongo; Leevan Tibaijuka; Musa Kayondo; Godfrey Twesigomwe; Joseph Ngonzi; Henry Mark Lugobe (Hindawi Limited, 2021)
Background. Preeclampsia is a priority obstetric emergency requiring urgent diagnosis and treatment to avert poor pregnancy outcomes. Nonproteinuric preeclampsia poses even greater diagnostic challenges due to contested diagnostic criteria by the clinical practice guidelines and variable clinical presentation. Previously, preeclampsia was only diagnosed if high blood pressure and proteinuria were present. This study determined the prevalence of nonproteinuric preeclampsia and associated factors among women admitted with hypertensive disorders of pregnancy at a referral hospital in southwestern Uganda. Methods. Women with hypertensive disorders of pregnancy were consecutively enrolled in a cross-sectional study at Mbarara Regional Referral Hospital between November 2019 and May 2020. We interviewed all pregnant women ≥20 gestation weeks presenting with hypertension and obtained their sociodemographic, medical, and obstetric characteristics. We excluded women with chronic hypertension. We measured bedside dipstick proteinuria in clean-catch urine. Preeclampsia was defined as hypertension plus any feature of severity including <100,000 platelets/ul, creatinine >1.1 g/dl, and liver transaminases ≥twice upper normal limit with or without proteinuria. We defined nonproteinuric preeclampsia in participants with <+2 urine dipstick cut-off and determined the factors associated with nonproteinuric preeclampsia using logistic regression. Results. We enrolled 134 participants. The mean age was 26.9 (SD ± 7.1) years and 51.5% were primigravid. The prevalence of nonproteinuric preeclampsia was 24.6% (95% CI: 17.9-32.7). Primigravidity (aOR 2.70 95% CI: 1.09-6.72, p = 0.032) was the factor independently associated with nonproteinuric preeclampsia. Conclusion. Nonproteinuric preeclampsia was common, especially among primigravidae. We recommend increased surveillance for nonproteinuric preeclampsia, especially among first-time pregnant women, who may not be detected by the traditional criteria. Obstetrics care providers should emphasize laboratory testing beyond proteinuria, among all women with hypertensive disorders of pregnancy to optimally diagnose and manage nonproteinuric preeclampsia.